2022
DOI: 10.34067/kid.0004412021
|View full text |Cite
|
Sign up to set email alerts
|

Iron Supplementation Improves Skeletal Muscle Contractile Properties in Mice with CKD

Abstract: Background: Chronic kidney disease (CKD) patients frequently have compromised physical performance, which increases their mortality; however, their skeletal muscle dysfunction has not been characterized at the single fiber and molecular levels. Notably, interventions to mitigate CKD myopathy are scarce. Methods: The impact of CKD in the absence and presence of iron supplementation on the contractile function of individual skeletal muscle fibers from the soleus and extensor digitorum longus muscles was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 61 publications
0
21
1
Order By: Relevance
“…However, a host of counteracting measures have shown to improve muscle performance in CKD patients or animal models and could be also assessed at the muscle biopsy level of CKD patients (alone or in combination with other interventions). For example, a recent study (45) with iron supplementation in an animal model of CKD showed significant improvements in muscle contraction properties of single muscle fibers indicating that timely maintenance of iron balance in CKD patients could also maintain or improve skeletal muscle quality and quantity. Therefore, future studies could verify the results in muscle biopsies of human patients (preferably during catheter insertion or transplantation to avoid further discomfort of patients).…”
Section: Discussionmentioning
confidence: 99%
“…However, a host of counteracting measures have shown to improve muscle performance in CKD patients or animal models and could be also assessed at the muscle biopsy level of CKD patients (alone or in combination with other interventions). For example, a recent study (45) with iron supplementation in an animal model of CKD showed significant improvements in muscle contraction properties of single muscle fibers indicating that timely maintenance of iron balance in CKD patients could also maintain or improve skeletal muscle quality and quantity. Therefore, future studies could verify the results in muscle biopsies of human patients (preferably during catheter insertion or transplantation to avoid further discomfort of patients).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously validated the use of the adenine diet in juvenile male mice indicating that various phenotypes are similar to humans including growth retardation, cachexia, anemia, iron deficiency and inflammation (Akchurin et al, 2016 ). Both groups received intraperitoneal injections of iron dextran at 0.5 g/kg weekly to eliminate the potential confounding effect of iron deficiency and anemia on muscle contractile function (Dziegala et al, 2018 ; Finch et al, 1976 ; Momb et al, 2022 ; Patino et al, 2020 ). Mouse body length was measured by the nose (snout) to tail tip length of anesthetized mice.…”
Section: Methodsmentioning
confidence: 99%
“…Determining the individual impact of each of these components using whole body and whole muscle function can be difficult, so a reductionist approach may be needed to determine the specific mechanisms behind the loss of physical capacity. One means of examining myopathy independent of neuropathy and other confounders is to examine single fiber contractile function as these measurements are performed on fibers without an excitable membrane, due to being chemically skinned, and within their normal three‐dimensional structure, protein content, and ionic conditions (Höök et al, 2001 ; Miller et al, 2013 ; Miller et al, 2015 ; Mitrou et al, 2019 ; Momb et al, 2022 ; Toth et al, 2013 ). Single fiber force production (cellular level) and the underlying myofilament mechanical properties (molecular level), including myosin‐actin cross‐bridge kinetics, can be assessed within the same fiber (Kawai & Halvorson, 1991 ; Miller et al, 2010 ; Momb et al, 2022 ; Zhao & Kawai, 1994 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations